2021
DOI: 10.1016/j.stemcr.2021.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming epiblast stem cells into pre-implantation blastocyst cell-like cells

Abstract: Summary Recently, a new wave of synthetic embryo systems (SESs) has been established from cultured cells for efficient and ethical embryonic development research. We recently reported our epiblast stem cell (EPISC) reprogramming SES that generates numerous blastocyst (BC)-like hemispheres (BCLH) with pluripotent and extraembryonic cell features detected by microscopy. Here, we further explored the system over key time points with single-cell RNA-sequencing analysis. We found broad induction of the 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, unlike naive mouse ESCs, naive human ESCs have recently been shown by multiple groups to readily give rise to trophoblast ( Cinkornpumin et al., 2020 ; Dong et al., 2020 ; Guo et al., 2021 ; Io et al., 2021 ), suggesting greater plasticity of human ESCs. In addition, it has been shown that media containing BMP4 induces chromatin remodeling in primed mouse ESCs ( Kime et al., 2016 ; Yu et al., 2020 ), inducing some cells toward a naive, and even 2C-like, fate, while producing TE-like features in other cells ( Kime et al., 2019 ; Tomoda et al., 2021 ). Our own analysis of primed hPSCs treated with a BMP4-containing medium points to a direct conversion of these cells to a TE-like fate, following 4 days of treatment with BMP4 and IWP2, with induction of only one naive pluripotency marker noted.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike naive mouse ESCs, naive human ESCs have recently been shown by multiple groups to readily give rise to trophoblast ( Cinkornpumin et al., 2020 ; Dong et al., 2020 ; Guo et al., 2021 ; Io et al., 2021 ), suggesting greater plasticity of human ESCs. In addition, it has been shown that media containing BMP4 induces chromatin remodeling in primed mouse ESCs ( Kime et al., 2016 ; Yu et al., 2020 ), inducing some cells toward a naive, and even 2C-like, fate, while producing TE-like features in other cells ( Kime et al., 2019 ; Tomoda et al., 2021 ). Our own analysis of primed hPSCs treated with a BMP4-containing medium points to a direct conversion of these cells to a TE-like fate, following 4 days of treatment with BMP4 and IWP2, with induction of only one naive pluripotency marker noted.…”
Section: Discussionmentioning
confidence: 99%
“…Nature. 2020;577(7791):459–60 [ 32 ] Tomoda K, Hu H, Sahara Y, Sanyal H, Takasato M, Kime C. Reprogramming epiblast stem cells into pre-implantation blastocyst cell-like cells. Stem Cell Rep. 2021;16(5):1197–209 [ 42 ] Tomoda K, Kime C. Synthetic embryology: Early mammalian embryo modeling systems from cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous publications 3 , 4 we demonstrated the implementation, integration, and utilization of SkewC in scRNA-seq data analysis.…”
Section: Before You Beginmentioning
confidence: 99%